Product Lifecycle Management: Towards Knowledge-Rich Enterprises IFIP WG 5.1 International Conference, PLM 2012, Montreal, QC, Canada, July 9-11, 2012, Revised Selected Papers - Rivest, Louis.; Rivest, Louis.; Bouras, Abdelaziz.; Bouras, Abdelaziz.; Louhichi, Borhen.; Louhichi, Borhen. (IFIP Advances in Information and Communication Technology,, 2012)
This book constitutes the refereed post-proceedings of the 9th IFIP WG 5.1 International Conference on Product Lifecycle Management, PLM 2012, held in Montreal, Canada, in July 2012. The 58 full papers presented were carefully reviewed and selected from numerous submissions. They cover a large range of topics such as collaboration in PLM, tools and methodologies for PLM, modeling for PLM, and PLM implementation issues.